Internet-era patterns of protection and inheritance methods for Minangkabau talempong pacik music - Teti Darlenis (International Journal of Visual and Performing Arts, 2022)
The preservation and transmission of talempong pacik music culture have a significant impact on the preservation of Minangkabau music culture. In addition, on a national scale, it contributes to the promotion of the healthy growth of the national culture. This research seeks to determine how the protection and inheritance model of the Minangkabau talempong pacik has evolved in the Internet era. The necessary data consist of (1) Minangkabau talempong pacik data and (2) talempong pacik inheritance pattern data. Literature review and observation of talempong pacik music performances on digital platforms such as YouTube, Instagram, and Facebook provided the data. The analysis is conducted by stressing the pattern resulting from the talempong pacik's maintenance and transmission. Ultimately, the results of this study show that the quality of talempong pacik's musical legacy will improve greatly as a result of the extensive and continuous use of new media to assist its preservation. New media used to study traditional talempong pacik music, including videos of talempong pacik performances, animation of talempong musical instrument games, and talempong pacik music software as a form of learning innovation, demonstrate that the quality of inheritance is highly adaptable to technological advancements